Impact of Celebrity Endorsement and Reference Group on Customer Purchase Intention for Non-durable Goods - Shrestha, Sajeeb Kumar; Manandhar, Binita; Basnet, Mahesh (Ganeshman Darpan, 2023)
Consumer purchasing behaviour is impacted by a range of factors that must be identified. This study's main goal was to investigate how reference groups and celebrity endorsements affect consumers' choices for non-durable goods. Reference groups and celebrity endorsements both have a significant impact on how consumers choose products. The study's population encompassed customers from different age groups and sectors, including students, homemakers, bankers, teachers, and professionals in various fields. A total of 430 respondents received self-administered questionnaires through convenient sampling techniques, and 400 completed questionnaires were collected. The study's findings indicated that the reference group is a potent factor with a significant influence on consumer buying decisions, while the correlation between celebrity endorsements and consumer purchasing decisions was found to be weak.